Surgery for Simple Anal Fistula under Local Anesthesia - Javed Iqbal, Tariq Jamil, Farah Saleem, Syed Aamer Hussain, Sarmad Younis, Zakriya Rashid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infections of the anal glands, which drain into the anal crypts, account for more than 95% of all cases of anorectal abscess. Although fistula-in-ano is usually harmless, it can nonetheless cause severe pain and significantly impact patients' day-to-day lives. Even though most anorectal procedures are performed when the patient is under general or regional anesthesia, there is mounting proof that these procedures can be done safely and effectively in an outpatient setting using only local anesthesia. All procedures in the current investigation were performed with local anesthesia, specifically, 2% lidocaine and 0.5 % bupivacaine. Place and Duration of study: Departments of General Surgery, HMC Peshawar and Nishtar Hospital, Multan for the duration of six months from June 2021 to November 2021. Method: Including the time needed to inject the anesthetic, the typical surgical procedure lasted around 26 minutes. No patient reported more than a 7 on a visual analogue scale for pain on the day of surgery, or the first postoperative day. In most cases, patients spend around two days in the hospital. Results: Including the time needed to inject the anesthetic, the typical surgical procedure lasted around 26 minutes. No patient reported more than a 7 on a visual analogue scale for pain on the day of surgery, the day of surgery, or the first postoperative day. In most cases, patients spend around two days in the hospital. Conclusion: With early ambulation, good tolerability, and fewer anaesthetic problems, local fistula in- ano repair anesthesia is a safe and effective option. In-Ano Fistula, VAS, and Local Anesthetics are some of the terms that will be discussed.